THE LEVEL OF FISHERMEN'S SATISFACTION WITH THE PROVISION OF SEA FISHING SERVICES IN THE BUNGUS OCEAN FISHING PORT OF WEST SUMATRA PROVINCE - Cahni Oktarina; Alit Hindri Yani; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in April 2019 which aims to determine the level of fishermen's satisfaction with sea food supply services at Bungus Ocean Fisheries Port (PPS), West Sumatra Province using the survey method. Determination of the value of satisfaction level is determined using the analysis of the Customer Satisfaction Index (CSI) and analysis of Importance Performance Analysis (IPA). The results showed that the value of the Customer Satisfaction Index (CSI) of each item was very high at 0.84 for clean water, 0.89 for the value of the Customer Satisfaction Index (CSI) of diesel and the value of the Customer Satisfaction Index (CSI) of 0, 87. This number is in the range of 0.81-1.00 which is categorized as very satisfactory. And the results of the IPA analysis show that in each item scattered the attributes of four airports except that clean water is not found in quadrant I.Keywords: West Sumatra Province, level of satisfaction, PPS Bungus